The Social Services : The immediate problem and the way forward / a memorandum prepared by the Socialist Medical Association (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages THE SOCIAL SERVICES THE IMMEDIATE PROBLEM AND THE WAY FORWARD A MEMORANDUM PREPARED BY THE SOCIALIST MEDICAL ASSOCIATION, 59, NEW OXFORD STREET LONDON, W.C.1. 15X/2/464/1